2023
DOI: 10.1177/20552076231176160
|View full text |Cite
|
Sign up to set email alerts
|

The feasibility of remotely monitoring physical, cognitive, and psychosocial function in individuals with stroke or chronic obstructive pulmonary disease

Abstract: Objective Clinical implementation of remote monitoring of human function requires an understanding of its feasibility. We evaluated adherence and the resources required to monitor physical, cognitive, and psychosocial function in individuals with either chronic obstructive pulmonary disease or stroke during a three-month period. Methods Seventy-three individuals agreed to wear a Fitbit to monitor physical function and to complete monthly online assessments of cognitive and psychosocial function. During a three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 71 publications
0
1
0
Order By: Relevance
“…Reminders were sent to participants to synchronise their devices and complete online assessments, with 65% of participants requiring at least one reminder to achieve a wear time of 77%. 59 This small study included a selective and relatively young population, questioning the feasibility of remote monitoring in older or less healthy individuals. A recent study of 82 people (mean age 80 years) with dementia, including vascular dementia, demonstrated that remote monitoring of physiological parameters was feasible with carer support but needs confirmation.…”
Section: Could Technologies Help Data Completeness In Csvd Trials?mentioning
confidence: 99%
“…Reminders were sent to participants to synchronise their devices and complete online assessments, with 65% of participants requiring at least one reminder to achieve a wear time of 77%. 59 This small study included a selective and relatively young population, questioning the feasibility of remote monitoring in older or less healthy individuals. A recent study of 82 people (mean age 80 years) with dementia, including vascular dementia, demonstrated that remote monitoring of physiological parameters was feasible with carer support but needs confirmation.…”
Section: Could Technologies Help Data Completeness In Csvd Trials?mentioning
confidence: 99%